STRATEGI PERENCANAAN KEUANGAN PADA UKM PUTRI TIMUS DI KARANGANYAR - Sugiarti, Sugiarti; Suparti, Erni; Sunardi, Sunardi; Giyanti, Ida; Yulandari, Ariefah (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Thymus is one of the famous traditional foods in Karanganyar Regency, Central Java Province. Putri Timus is one of the Small Medium Enterprises in Karanganyar district that produces purple thymus. The product from Putri Timus has one specialty, namely the inside of the thymus contains Bligo fruit (Benincasa hispida) with various benefits. The method used in this program is to provide counseling and assistance regarding financial planning to MSME players to a simple but understandable application stage. The results of this community service program provide a simple solution to be careful in managing finances by considering several worst possibilities. Participants feel that they have a solution when they want to plan their finances both in the short and long term.